Efeito de extratos vegetais na parasitemia do Trypanosoma cruzi e na biodistribuição do pertecnetato de sódio (Na99mTcO4) - Silva, Roseane Pereira da (2009)
Artemisia vulgaris (AV) is an antihelmintic and antimalarial drug; Aloe vera(babosa) acts as antidiabetic, laxative and anti-inflammatory; Benznidazole (BZ) is a trypanocidal of Trypanosoma cruzi (TC). Technetium-99m (99mTc) has been used in nuclear medicine to obtain diagnostic images. This study evaluated the plant effects in TC parasitemia and in the biodistribution of 99mTc in mice. Twenty mice were infected by TC. At the peak of parasitemia, 5 mice received babosa; 5 received AV and 5 received BZ. The parasitemia was determined in 0, 2, 4 and 6 h of drugs administration. Five infected mice without drugs, 5 mice without TC and the group treated with AV, received 99mTc. The radioactivity was calculated. Infected mice that received babosa reduced significantly (p<0.05) the parasitemia. The percentage of activity (%ATI) decreased significantly in the AV group. These results indicate that babosa possibly is an anti-TC drug and AV reduces the %ATI probably due to its biological effects